2017
DOI: 10.1186/s40663-017-0097-8
|View full text |Cite
|
Sign up to set email alerts
|

Stand dynamics of the drought-affected floodplain forests of Araguaia River, Brazilian Amazon

Abstract: Background: The floodplain forests of Araguaia River, a clear-water river in the southeastern Amazon (Tocantins State, Brazil), are characterized by seasonal flooding up to 3.5 m height, low nutrient levels in the water, and seasonal drought periods of 4-5 months. Methods: We studied the forest dynamics (tree diameter growth, tree mortality and recruitment) of this unique forest ecosystem over a 5-year period by repeated censuses in 12 permanent plots established along a flooding gradient. Results: The cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Our results suggest that tree mortality caused by the combination of extreme rainfall/river discharge associated with damming is substantially higher than average mortality in floodplain forests (eg. Homeier, Kurzatkowski, & Leuschner, ; Nebel, Kvist, Vanclay, & Vidaurre, ). Even during unusually severe flooding seasons, tree mortality in tropical riparian forests seems to be lower than detected here, probably because flooding intensity is within species flooding tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that tree mortality caused by the combination of extreme rainfall/river discharge associated with damming is substantially higher than average mortality in floodplain forests (eg. Homeier, Kurzatkowski, & Leuschner, ; Nebel, Kvist, Vanclay, & Vidaurre, ). Even during unusually severe flooding seasons, tree mortality in tropical riparian forests seems to be lower than detected here, probably because flooding intensity is within species flooding tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The local topography is flat and the predominant soil type in this region is Gleysol (Food and Agriculture Organization (FAO) classification) [45]. studies have suggested that this forest shows two periods of water stress-one due to excess of water in the peak of the rainy season-and another due to water deficit, at the end of the dry season [42][43][44]. During the El Niño drought of 2005, decreased rates of evapotranspiration [42] and increasing rates of tree mortality were reported in this region [44].…”
Section: Study Sitementioning
confidence: 99%
“…studies have suggested that this forest shows two periods of water stress-one due to excess of water in the peak of the rainy season-and another due to water deficit, at the end of the dry season [42][43][44]. During the El Niño drought of 2005, decreased rates of evapotranspiration [42] and increasing rates of tree mortality were reported in this region [44]. Given the uncertainties of floodplain environmental response to seasonal cycles of flood and dry periods, this study aims to evaluate the seasonal productivity of this floodplain forest located in the Amazon-Cerrado transition, as well as its environmental controls, based on field observations and on enhanced vegetation index (EVI) derived from MODIS (MAIAC) surface reflectance data.…”
Section: Study Sitementioning
confidence: 99%